1999
DOI: 10.1128/jb.181.9.2863-2871.1999
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Expression of the Fructan Hydrolase Gene of Streptococcus mutans GS-5 by Induction and Carbon Catabolite Repression

Abstract: The polymers of fructose, levan and inulin, as well as sucrose and raffinose, are substrates for the product of the fruA gene of Streptococcus mutans GS-5. The purpose of this study was to characterize the DNA immediately flanking fruA, to explore the regulation of expression of fruA by the carbohydrate source, and to begin to elucidate the molecular basis for differential expression of the gene. Located 3′ to fruA was an open reading frame (ORF) with similarity to β-fructosidases which was cotranscribed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(63 citation statements)
references
References 58 publications
0
62
1
Order By: Relevance
“…Together with the real-time PCR results, these data demonstrate that the LevQRST pathway is required for the induction of EII Lev by fructose. At first, these results may seem contradictory, because, as we have described, expression of fruA in S. mutans is dramatically higher when the cells are grown in inulin or levans, than when fructose is the growth substrate (Jacques et al, 1985;Burne and Penders, 1992;Burne et al, 1999;Wen and Burne, 2002). One interpretation is that the LevQRST system binds fructose or fructose-containing polymers to mediate induction of its targets.…”
Section: The Levqrst Operon Is Also Required For the Induction Of Eiimentioning
confidence: 85%
“…Together with the real-time PCR results, these data demonstrate that the LevQRST pathway is required for the induction of EII Lev by fructose. At first, these results may seem contradictory, because, as we have described, expression of fruA in S. mutans is dramatically higher when the cells are grown in inulin or levans, than when fructose is the growth substrate (Jacques et al, 1985;Burne and Penders, 1992;Burne et al, 1999;Wen and Burne, 2002). One interpretation is that the LevQRST system binds fructose or fructose-containing polymers to mediate induction of its targets.…”
Section: The Levqrst Operon Is Also Required For the Induction Of Eiimentioning
confidence: 85%
“…It has been shown that expression of the genes encoding di¡erent fructanases is tightly regulated by environmental factors [25]. Fructanase used in our study was isolated from S. mutans.…”
Section: Discussionmentioning
confidence: 99%
“…Since the concentration of fructose provided for growth was 0.2% (11 mM) or higher, it would not be surprising to see that the fruI/fruCD double mutants still possessed signi¢cant growth capacity, even if the K m for fructose of II Man or of the EII for sorbitol was comparatively high. Note: S. mutans UA159 and its mutant strains were grown on TV medium [13] with indicated sugar as the sole carbohydrate source. PEP-dependent fructose^and glucose^PTS activities, F^PTS and G^PTS, respectively, were measured using the method of Leblanc et al [15] and expressed as nmol min 31 mg 31 cell dry wt.…”
Section: Isolation and Characterization Of Frui-and Frucd-defective Mmentioning
confidence: 99%